LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SELF MANAGEMENT TERHADAP PERILAKU KONFORMITAS SISWA KELAS XI MA AL-MUKHTARIYAH MANDE - Putri Nabila Nursadeli; Siti Fatimah; Maya Masyita Suherman (IKIP Siliwangi, 2021)
Conformity is conformity to attitudes and behavior with the values of the rules that apply in the Conformity is conformity to attitudes and behavior with the values of the rules that apply in the individual's social environment. Conformity in adolescent peers seeks and obtains information about the group with the aim that the individual can behave in accordance with the norms that apply in the group. Conformity in the peer environment has two characteristics, namely positive conformity and negative conformity. The purpose of the study was to find out how the implementation of group guidance services was carried out, to find out how students responded during the implementation of group guidance and to know the results of the implementation of group guidance services. The method used in this study is a qualitative descriptive method. Data collection techniques used in this research are interview, observation and documentation techniques. The subjects in this study were one teacher of guidance and counseling and five students of class XII MIPA 1. Based on the results obtained by researchers, it can be concluded that students have performed conformity behavior, both in a positive direction and in a negative direction. The provision of self-management technique group guidance services is useful for students in adding insight and information about conformity behavior, increasing students' awareness of which conformity behavior is good to do and good to leave. Keywords: : Peer conformity, group guidance, self management techniques